UNIFACVEST EDUCATIONAL TECHNOLOGY AND ACTIVE LEARNING: A REPORT ON THE TRAINING PRACTICES OF THE COURSE FORMATIVE ACTIVITY VII IN THE 2025.2 SEMESTER - Rodrigues, Renato; da Silva, Edi; Rodrigues Neto, Artur (Seven Editora, 2025)
This article presents a systematized report of the activities developed in the course Educational Technology – Formative Activity VII, from the Centro Universitário UNIFACVEST, during the 2025.2 academic semester. The actions involved planning, execution and analysis of pedagogical practices integrating digital technologies, maker culture, active methodologies, computational thinking and theoretical foundations from Developmental Psychology, especially Piaget and Vygotsky. Among the activities carried out, the following stand out: construction of sensory panels, development of digital and physical games using Scratch, Micro:bit, laser cutting and 3D printing, field visits, pedagogical workshops, application of projects in public schools, and production of lesson plans in ENADE format. The practices demonstrated the transformative potential of educational technology in promoting autonomy, creativity, scientific investigation and meaningful learning. The results indicate that the course successfully articulated theory and practice in a critical and innovative manner. DOI: https://doi.org/10.56238/sevened2025.036-120